2013
DOI: 10.1186/1742-4690-10-128
|View full text |Cite
|
Sign up to set email alerts
|

Efficient BST2 antagonism by Vpu is critical for early HIV-1 dissemination in humanized mice

Abstract: BackgroundVpu is a multifunctional accessory protein that enhances the release of HIV-1 by counteracting the entrapment of nascent virions on infected cell surface mediated by BST2/Tetherin. Vpu-mediated BST2 antagonism involves physical association with BST2 and subsequent mislocalization of the restriction factor to intracellular compartments followed by SCF(β-TrCP) E3 ligase-dependent lysosomal degradation. Apart from BST2 antagonism, Vpu also induces down regulation of several immune molecules, including C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 50 publications
1
51
0
Order By: Relevance
“…This attribute of O-Nef proteins may be responsible for the inefficient viral spread observed in vitro under conditions of limiting virus input. Previous studies using humanized mice suggested that BST2 antagonism by Vpu facilitated HIV-1 replication and propagation in vivo, in particular during early stages following infection, where transmission by cell-free virus may play a critical role (4,5). In contrast to M-Vpu, O-Nef may not be effective at promoting the initial burst of viral proliferation and expansion that is most likely necessary to enable dissemination to local lymphoid tissues and the establishment of systemic infection (49).…”
Section: Discussionmentioning
confidence: 97%
“…This attribute of O-Nef proteins may be responsible for the inefficient viral spread observed in vitro under conditions of limiting virus input. Previous studies using humanized mice suggested that BST2 antagonism by Vpu facilitated HIV-1 replication and propagation in vivo, in particular during early stages following infection, where transmission by cell-free virus may play a critical role (4,5). In contrast to M-Vpu, O-Nef may not be effective at promoting the initial burst of viral proliferation and expansion that is most likely necessary to enable dissemination to local lymphoid tissues and the establishment of systemic infection (49).…”
Section: Discussionmentioning
confidence: 97%
“…HIV-1 is able to circumvent tetherinmediated entrapment through the disruption of tetherin trafficking by the viral protein Vpu. Vpu antagonism of tetherin has been implicated in viral expansion and dissemination in vivo (18)(19)(20)(21).…”
mentioning
confidence: 99%
“…All transmitter/founder (T/F) HIV-1 strains contain a functionally competent vpu coding sequence (3), and humanized mouse models have demonstrated the contribution of Vpu to early viral dissemination after infection (4,5).…”
mentioning
confidence: 99%